5. A SCOPING REVIEW: COMPARISON OF COAGULATION PARAMETERS RESULTS IN DECEASED AND RECOVERED COVID-19 PATIENTS (Vietnam Journal of Community Medicine, 2024)
Objective: Compare coagulation markers between deceased and recovered COVID-19 patients.Methods: A search of PubMed was conducted to identify peer-reviewed articles published between January 1, 2022, and April 1, 2024. Articles were selected based on predefined inclusion and exclusion criteria. Data extraction focused on coagulation parameters, including platelet count, fibrinogen (Fib), D-Dimer, prothrombin time (PT), and activated partial thromboplastin time (APTT) across six selected studies involving a total of 7,052 patients.Results: The findings indicated that recovered patients had significantly higher platelet counts compared to deceased patients (p < 0.05). D-Dimer and Fib levels were lower in recovered patients, while PT results were significantly prolonged in deceased individuals (p < 0.05). APTT results showed variability, with some studies reporting higher levels in deceased patients, while others indicated longer APTT in recovered patients, remaining within normal ranges.Conclusion: Coagulation markers exhibit significant differences between deceased and recovered COVID-19 patients, suggesting their potential utility in predicting disease severity and guiding clinical management.
Keywords: coagulation parameters; deceased COVID-19 patients; recovered COVID-19 patients